Democracy and higher education : traditions and stories of civic engagement - Peters, Scott J. (Scott Joseph) (Transformations in higher education., 2010)
How are we to understand the nature and value of higher education's public purposes, mission, and work in a democratic society? How do-and how should-academic professionals contribute to and participate in civic life in their practices as scholars, scientists, and educators? Democracy and Higher Education addresses these questions by combining an examination of several normative traditions of civic engagement in American higher education with the presentation and interpretation of a dozen oral history profiles of contemporary practitioners. In his analysis of these profiles, Scott Peters reveals and interprets a democratic-minded civic professionalism that includes and interweaves expert, social critic, responsive service, and proactive leadership roles. Democracy and Higher Education contributes to a new line of research on the critically important task of strengthening and defending higher education's positive roles in and for a democratic society.